Reduced Graphene Oxide/Carbon Nanotube Composites as Electrochemical Energy Storage Electrode Applications - Wenyao Yang; Yan Chen; Jingfeng Wang; Tianjun Peng; Jianhua Xu; Bangchao Yang; Ke Tang (Nanoscale Research Letters, 2018)
Abstract We demonstrate an electrochemical reduction method to reduce graphene oxide (GO) to electrochemically reduced graphene oxide (ERGO) with the assistance of carbon nanotubes (CNTs). The faster and more efficient reduction of GO can be achieved after proper addition of CNTs into GO during the reduction process. This nanotube/nanosheet composite was deposited on electrode as active material for electrochemical energy storage applications. It has been found that the specific capacitance of the composite film was strongly affected by the mass ratio of GO/CNTs and the scanning ratio of cyclic voltammetry. The obtained ERGO/CNT composite electrode exhibited a 279.4 F/g-specific capacitance and showed good cycle rate performance with the evidence that the specific capacitance maintained above 90% after 6000 cycles. The synergistic effect between ERGO and CNTs as well as crossing over of CNTs into ERGO is attributed to the high electrochemical performance of composite electrode.